2021
DOI: 10.1007/s41130-021-00156-w
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable food labelling: considerations for policy-makers

Abstract: Improving the sustainability of the global food system is a policy priority. There are multiple types of sustainability labels in the food market, and policy-makers need to know what constitutes an effective label. We discuss the use of labels to inform consumers about the economic, social and environmental sustainability implications of their food purchasing choices. We categorise these sustainability labels and explain the opportunities they offer and the challenges they pose to be effective. Improved consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…With respect to the second point (ii), on sub‐signals, the overall results emphasize the social and emotional dimensions as common sub‐signals for all three attributes/signals. Specifically, social sustainability is more relevant than economic sustainability, consistent with previous research (de Magistris & Gracia, 2016; Stein & de Lima, 2021), and social protection is confirmed as an important driver of sustainable food consumption (Guyader et al, 2017; Hu et al, 2019; Van Loo et al, 2015). Our study confirms this by the high level of visual and cognitive attention devoted to those areas of interest representing such dimensions of sustainability.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…With respect to the second point (ii), on sub‐signals, the overall results emphasize the social and emotional dimensions as common sub‐signals for all three attributes/signals. Specifically, social sustainability is more relevant than economic sustainability, consistent with previous research (de Magistris & Gracia, 2016; Stein & de Lima, 2021), and social protection is confirmed as an important driver of sustainable food consumption (Guyader et al, 2017; Hu et al, 2019; Van Loo et al, 2015). Our study confirms this by the high level of visual and cognitive attention devoted to those areas of interest representing such dimensions of sustainability.…”
Section: Discussionsupporting
confidence: 85%
“…For example, aspects concerning the economic conditions of workers/farmers and the overall social well‐being of local producers could be used as communication components to attract consumers' visual and cognitive attention. The focus of communications should change from merely the environmental performance of food production to the social and economic benefits of typical–local foods; this aligns with more recent debates in research and industry (e.g., de Magistris & Gracia, 2016; Stein & de Lima, 2021). Organizations would benefit from connecting with various actors in the local economic system (e.g., catering, trade, crafts) and working together towards strengthening the local destination's image (focusing more on geographical indications and related health and well‐being experiences/benefits) to enhance branding and attractiveness to consumers.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…8 It was unclear from the question asked whether the labeling was conceived as mandatory or voluntary, and how the existing national labeling systems should have been considered. Despite soliciting layperson's opinions, it is regularly questioned whether labeling can contribute to sustainability by encouraging sustainable consumption (Stein & de Lima, 2021). On this issue, a subgroup will assist the Commission in collecting data and opinions, assuming a behavioral perspective as suggested by Purnhagen in this special issue (Purnhagen, 2022), and hopefully a more robust methodology than that employed in the consultation (European Commission, 2021b).…”
Section: The European Commission's Revision Of Animal Welfare Legisla...mentioning
confidence: 99%